2012
DOI: 10.1017/s1047951112001424
|View full text |Cite
|
Sign up to set email alerts
|

Amplatzer occluder versus CardioSEAL/STARFlex occluder: a meta-analysis of the efficacy and safety of transcatheter occlusion for patent foramen ovale and atrial septal defect

Abstract: The meta-analysis has proven the Amplatzer to be the superior occluder, serving better prognosis with more fluent procedure and less complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…In a subgroup analysis of our study based on the type of occluder device used, we demonstrated larger risk estimates of new-onset AF/ AFL with nondisc occluder devices (RR 10.03) compared with Amplatzer device (RR 2.77). This novel finding is in concordance with multiple previous studies that have shown the Amplatzer device might be associated with less incidence of new-onset AF/AFL compared with other devices [25,30,35,36]. The incidence of new-onset AF/AFL was significantly higher with PFO closure compared to medical therapy in the CLOSURE-1 trial (that utilized Starflex device), and Gore REDUCE trial (that utilized Helex and Cardioform devices), however, in the extended follow-up of the RESPECT trial that exclusively utilized Amplatzer PFO occluder [13], the risk of new-onset AF/AFL was similar compared with medical therapy alone.…”
Section: Discussionsupporting
confidence: 92%
“…In a subgroup analysis of our study based on the type of occluder device used, we demonstrated larger risk estimates of new-onset AF/ AFL with nondisc occluder devices (RR 10.03) compared with Amplatzer device (RR 2.77). This novel finding is in concordance with multiple previous studies that have shown the Amplatzer device might be associated with less incidence of new-onset AF/AFL compared with other devices [25,30,35,36]. The incidence of new-onset AF/AFL was significantly higher with PFO closure compared to medical therapy in the CLOSURE-1 trial (that utilized Starflex device), and Gore REDUCE trial (that utilized Helex and Cardioform devices), however, in the extended follow-up of the RESPECT trial that exclusively utilized Amplatzer PFO occluder [13], the risk of new-onset AF/AFL was similar compared with medical therapy alone.…”
Section: Discussionsupporting
confidence: 92%
“…An increased risk of atrial fibrillation from the STARFlex device had been shown previously, and this occluder was also known for a higher risk of device thrombus. 22 Our pooled analysis showed that the rate of atrial fibrillation for all devices was significantly higher than that for medical therapy alone. Another consideration is the overall low absolute-event rate of recurrent neurologic events.…”
Section: A B Cmentioning
confidence: 73%
“…The CardioSEAL and STARFlex occluders (NMT Medical, Boston, MA) were combined into one group due to their structural similarities, consistent with prior studies. [24][25][26][27] Data from agitated saline studies were available postprocedure and at 3-month and 1-year follow-up. As a secondary analysis to determine the time course of residual shunt, the rates of detected interatrial shunting were compared at each time point using the McNemar test.…”
Section: Methodsmentioning
confidence: 99%
“…21,[29][30][31][32] Others have also reported significantly higher residual shunt rates with CardioSEAL/STARFlex devices compared with the Amplatzer device, consistent with our results. 24,33 Our center experienced a low long-term mortality rate of 6% overall. Several other studies have examined mortality after device closure of ASDs.…”
Section: Comparison To Current Literaturementioning
confidence: 97%